Analisis limbah pertanian kelapa sebagai adsorben dalam penurunan total padatan pada geywater - Devy Cendekia; Dian Ayu Afifah; Fadian Farisan Silmi (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Agiculture waste is an unused by-product from the remnants of agicultural activities. The Impact of agiculture waste is becoming a substance contaminant that can disturb life biotic as well as become a source of disease. Agiculture waste is divided into three goups: waste agiculture pre-harvest, waste agiculture at the moment harvest, and waste agiculture post-harvest. Handling agiculture waste could be conducted by manipulating waste that becomes a product-appropriate use. Agiculture waste that can be utilized is shell coconut waste. Shell coconut waste could be made adsorbent in reducing solids pollutants in geywater. This study used a continuous adsorption column method with adsorbent media engineered from shell coconut waste. So that it can be known the potential of shell coconut waste as an adsorbent in reducing total solids in geywater. Based on analysis using an adsorption test with an isotherm model, the adsorbent product from engineering waste shell coconut can remove 64% of solids suspended in geywater. The adsorption process of the solid suspended follows the Langmuir isotherm model, with capacity adsorption from an adsorbent of 0.0412 mg g-1. Adsorbent waste agicultural products can reduce total solids dissolved in geywater by 3.7%. Therefore, adsorbent products from agiculture waste could become alternative adsorption media in reducing solids pollutants in geywater.